The expression of four pyridoxal kinase (PDXK) human variants in Drosophila impacts on genome integrity - Elisa Mascolo (Nature Portfolio, 2019)
Abstract In eukaryotes, pyridoxal kinase (PDXK) acts in vitamin B6 salvage pathway to produce pyridoxal 5′-phosphate (PLP), the active form of the vitamin, which is implicated in numerous crucial metabolic reactions. In Drosophila, mutations in the dPdxk gene cause chromosome aberrations (CABs) and increase glucose content in larval hemolymph. Both phenotypes are rescued by the expression of the wild type human PDXK counterpart. Here we expressed, in dPdxk 1 mutant flies, four PDXK human variants: three (D87H, V128I and H246Q) listed in databases, and one (A243G) found in a genetic screening in patients with diabetes. Differently from human wild type PDXK, none of the variants was able to completely rescue CABs and glucose content elicited by dPdxk 1 mutation. Biochemical analysis of D87H, V128I, H246Q and A243G proteins revealed reduced catalytic activity and/or reduced affinity for PLP precursors which justify this behavior. Although these variants are rare in population and carried in heterozygous condition, our findings suggest that in certain metabolic contexts and diseases in which PLP levels are reduced, the presence of these PDXK variants could threaten genome integrity and increase cancer risk.